Effects of endocrine modifiers on growth, carcass characteristics, and blood and tissue metabolites of finishing beef cattle - Bryant, Anthony C., author; Engle, Terry E., advisor (Colorado State University. Libraries, 2008)
The effects of vitamin A and the interaction of steroids and beta-adrenergic agonists on growth and carcass performance, tissue metabolite profiles, and lipogenic enzyme activity were evaluated in beef cattle. In 1 experiment steers were fed 1 of 5 supplemental levels of vitamin A (0, 1,103, 2,205, 4,410, or 8,820 IU/kg DM). Final BW, G:F, ADG, HCW, LM area, marbling, and quality grade distribution did not differ among treatments. Except for d 56, no correlations between marbling score and tissue retinol concentrations or vitamin A intake were found. A negative correlation between liver retinol and α-tocopherol was observed, which may have potential health implications. Results suggest that vitamin A supplementation up to twice the NRC-suggested concentration has little effect on performance, marbling, or lipogenic enzyme activity in yearling steers and further suggest that 2,205 IU supplemental vitamin A/kg of DM is adequate for growing/finishing beef steers.

In 2 separate experiments, factorial arrangements of implant and beta-adrenergic agonist dosages were evaluated for effects on performance, carcass traits, blood metabolites, and lipogenic enzyme activity. In Exp. 1, steers were assigned to ractopamine (RAC; 0, 100, or 200 mg·steer-1·d-1) and implant/reimplant (IMP; None/None, Revalor-S/None, or Revalor-IS/Revalor-S) regimens, whereas in Exp. 2, heifers were assigned to ractopamine (0 or 250 mg·heifer-1·d-1) and implant (none, Finaplix, or Revalor-200) treatments. No RAC x IMP interactions were noted for most carcass and performance traits. Cattle implanted or fed supplemental ractopamine had significantly greater final BW, HCW, ADG, and G:F than the respective controls. Despite no detectable difference in empty body fat (EBF), both marbling and quality grade were decreased significantly by IMP and numerically by RAC. Implanted cattle had decreased cortisol and increased GH, IGF-1, and NEFA. Although an IMP x RAC interaction was detected, BUN was decreased by IMP and RAC. No clear trends in lipogenesis were found. These data show that quality grade and marbling can differ significantly at equal EBF in finishing beef steers. Altogether, these data suggest that the modes of action of IMP and RAC are independent. Further research is needed to elucidate the exact mode of actions of these growth-enhancing products.
Keywords: beef cattle; blood; body composition; carcass characteristics; endocrine modifiers; finishing cattle; tissue metabolites; physiology; animal sciences